CdS/Mg-Fe layered double hydroxide: a versatile heterogeneous photocatalyst for the acylation of indoles with α-keto acids - Wang, Jun-Bo; Yue, Tong; Xu, Ling; Hao, Zhi-Qiang; Zhang, Zhan-Hui (Green chemistry : an international journal and green chemistry resource : GC, 2024)
The CdS/Mg-Fe layered double hydroxide (LDH) was successfully constructed by coupling CdS and Mg-Fe LDH based on the mutually complementary properties of the two materials. This stable and recyclable heterogeneous photocatalyst was found to realize the C3-acylation of indoles with α-keto acids. The reactions were carried out under irradiation with blue light at room temperature using abundant and inexpensive air as the oxidant. This methodology gives easy access to 3-acyl indoles with high yields. CdS/Mg-Fe LDH can be recovered and reused for multiple runs without obviously losing its photocatalytic activity. The composite CdS/MgFe layered double hydroxide was constructed and confirmed as an efficient recyclable heterogeneous photocatalyst for C-3 acylation of indoles with α-keto acids under light irradiation at room temperature.